Diagnostic yield of endoscopic ultrasound-guided tissue acquisition for small solid pancreatic lesions - Mie, Takafumi; Sasaki, Takashi; Kanata, Ryo; Furukawa, Takaaki; Takeda, Tsuyoshi; Kasuga, Akiyoshi; Matsuyama, Masato; Ozaka, Masato; Sasahira, Naoki (Endoscopy International Open, 2020)
Background and study aims Endoscopic ultrasound (EUS)-guided tissue acquisition is sometimes required to diagnose small solid pancreatic lesions. The aim of this study was to evaluate the diagnostic yield of EUS-guided tissue acquisition for small solid pancreatic lesions and the differences in diagnostic yield among different needles. Patients and method We retrospectively analyzed consecutive patients who had undergone EUS-guided tissue acquisition for solid pancreatic lesions less than 2 cm between November 2012 and June 2019. Three types of needles were evaluated in this study: a 22-gauge fine-needle aspiration (FNA) Lancet needle, a 20-gauge fine-needle biopsy (FNB) Menghini needle with a lateral forward bevel, and a 22-gauge FNB Franseen needle. We evaluated the diagnostic yield and safety of the procedure using these needles. Results We analyzed 160 patients with 163 lesions. The overall sensitivity, specificity, and accuracy were 92.0 %, 100 %, and 92.6 %, respectively. In the histological plus cytological diagnosis, accuracies of the Lancet, Menghini, and Franseen needles were 92.7 %, 97.0 %, and 85.7 %, respectively (P = 0.10). In the histological diagnosis alone, the negative predictive values (NPVs) of the Lancet, Menghini, and Franseen needles were 13.3 %, 53.3 %, and 27.3 %, respectively (P = 0.08). Adverse events occurred in four cases (2.5 %): one postprocedural bleeding, two cases of pancreatitis, and one pancreatic abscess. Conclusions EUS-guided tissue acquisition for small solid pancreatic lesions has a high diagnostic yield and safety. This study suggested a difference in the diagnostic yield of each needle for small solid pancreatic lesions.